Ice nucleation activity in various tissues of Rhododendron flower buds: their relevance to extraorgan freezing - Ishikawa, Masaya; Ishikawa, Mikiko; Toyomasu, Takayuki; Aoki, Takayuki; Price, William S. (Frontiers in Plant Science, 2015)
Wintering flower buds of cold hardy Rhododendron japonicum cooled slowly to subfreezing temperatures are known to undergo extraorgan freezing, whose mechanisms remain obscure. We revisited this material to demonstrate why bud scales freeze first in spite of their lower water content, why florets remain deeply supercooled and how seasonal adaptive responses occur in regard to extraorgan freezing in flower buds. We determined ice nucleation activity (INA) of various flower bud tissues using a test tube-based assay. Irrespective of collection sites, outer and inner bud scales that function as ice sinks in extraorgan freezing had high INA levels whilst florets that remain supercooled and act as a water source lacked INA. The INA level of bud scales was not high in late August when flower bud formation was ending, but increased to reach the highest level in late October just before the first autumnal freeze. The results support the following hypothesis: the high INA in bud scales functions as the subfreezing sensor, ensuring the primary freezing in bud scales at warmer subzero temperatures, which likely allows the migration of floret water to the bud scales and accumulation of icicles within the bud scales. The low INA in the florets helps them remain unfrozen by deep supercooling. The INA in the bud scales was resistant to grinding and autoclaving at 121∘C for 15 min, implying the intrinsic nature of the INA rather than of microbial origin, whilst the INA in stem bark was autoclaving-labile. Anti-nucleation activity (ANA) was implicated in the leachate of autoclaved bud scales, which suppresses the INA at millimolar levels of concentration and likely differs from the colligative effects of the solutes. The tissue INA levels likely contribute to the establishment of freezing behaviors by ensuring the order of freezing in the tissues: from the primary freeze to the last tissue remaining unfrozen.